1975
DOI: 10.1177/000348947508400202
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Metastasis from an Unknown Primary

Abstract: Summary--Forty-nine patients with cervical metastases from unknown primaries were treated during an 11-year period. Thirty-one (63%) of these patients were treated for cure rather than palliation. The three-year survival rate of these patients treated for cure was 39%. Although the treatment of these patients varied, a systematic mode of therapy has evolved: patients with histopathologic diagnosis of epidermoid carcinoma, or undifferentiated malignant tumor, metastatic to the neck from an unknown primary, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

1979
1979
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 15 publications
0
13
0
4
Order By: Relevance
“…With the recognition of the tonsil region as a significant site for primary tumors to emerge after treatment,9, 10 many subsequent series have included random biopsies of the tonsil as well. However, the overall yield of random biopsies in identifying occult primary tumor location was recognized to be quite low, ranging from 2% to 15% in patients without suspicious lesions on examination or radiography 17, 18…”
Section: Discussionmentioning
confidence: 99%
“…With the recognition of the tonsil region as a significant site for primary tumors to emerge after treatment,9, 10 many subsequent series have included random biopsies of the tonsil as well. However, the overall yield of random biopsies in identifying occult primary tumor location was recognized to be quite low, ranging from 2% to 15% in patients without suspicious lesions on examination or radiography 17, 18…”
Section: Discussionmentioning
confidence: 99%
“…2,4–7 Biopsies of the nasopharynx, base of tongue, and pyriform sinuses have routinely been advocated, since these sites are reported as the most prevalent areas to harbor the primary tumor in patients presenting with an unknown primary. 2,3,8 The yield from such directed biopsy specimens, however, has been consistently quite low, and identification of a primary tumor occurs in only 2% to 15% of specimens 6,9 …”
Section: Introductionmentioning
confidence: 99%
“…Large reported series indicated that the frequency is around 3% of the total head and neck cancer cases. [1–4] Owing to the rarity of the disease, all reports on treatment results of patients with squamous cell carcinoma of unknown primary tumor site presenting with cervical neck nodes are retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis of unknown primary on the whole carries a very poor prognosis, but in the head and neck region this is not the case. [1–4] The 5-year disease-specific survival rates range upwards to 74% in modern series, with overall survival rates being in the 40–66% range. [59]…”
Section: Introductionmentioning
confidence: 99%